Purpose in Life and Character Strengths as Predictors of Health Sciences Students’ Psychopathology During the COVID-19 Pandemic - Echeverria, Iván; Peraire, Marc; Penadés, Danaide; Quintero, Valentina; Benito, Ana; Almodóvar, Isabel; Haro, Gonzalo (Frontiers in Psychiatry, 2022)
Background Health sciences students experience high levels of psychopathology conditioned by psychosocial, financial, and academic factors. However, COVID-19 pandemic might even have worsened their mental health. Thus, this article aims to evaluate how the exposure to COVID-19 pandemic has affected these students’ mental health and to determine the effect of purpose in life and character strengths on this psychopathology. Methods A cross-sectional study of unpaired samples was carried out in Spain during the first and third waves of the pandemic in 70 medical and 52 nursing students. Results The risk factor that most determined the appearance of anxiety was the exposure of family and friends to COVID-19 (OR = 4.01; p < 0.001), while the most protective factors were honesty (OR = –1.14; p = 0.025) and purpose in life (OR = –0.18; p < 0.001). Purpose in life also protected against the onset of depression and total psychopathology. In addition, we observed studying medicine was a protective factor against total psychopathology while being a nursing student was associated with high levels of acute stress. Conclusion Exposure of the students’ family and friends to SARS-CoV-2 favored the appearance of symptoms of anxiety. Honesty had a preventing role in the onset of anxiety and a high purpose in life was protective against the appearance of anxiety, depression, and total psychopathology.